China in the Mekong River basin : the regional security implications of resource development on the Lancang Jiang - Goh, Evelyn (2009)
The Mekong River is a critical shared resource between China and five Southeast Asian countries, Myanmar, Laos, Thailand, Cambodia, and Vietnam. Over 80 million people depend on the river for their livelihoods, but recent large-scale resource development, especially in the form of hydropower development, pose serious problems within the river basin. This paper focuses on China's plans for hydropower development on its portion of the upper Mekong basin (Lancang Jiang) and their ecological, political and economic implications for Southeast Asian riparians. It shows that the economic imperative prevails among all riparian states, and that China and other countries tend to confine their cooperation to infrastructural development rather to consultation or management of potential adverse transboundary impacts of upstream development. However, the paper argues that 'securitising' this upstream-downstream problem is not the answer; rather, the way forward must involve first reconceptualising regional security in terms of comprehensive, human and economic security.